THE IMPORTANCE AND ESSENTIAL STEPS OF PILOT TESTING IN MANAGEMENT STUDIES: A QUANTITATIVE SURVEY RESULTS - Wadood, Fazli; Akbar, Fazal; Ullah, Imran (The journal of contemporary issues in business and government, 2021)
Pilot testing is the most appropriate tool and play indispensable role while conducting large scale survey to increase the reliability, validity and practicability of the questionnaire, especially in management, social sciences and education studies. Although there are several widely adopted rules of thumb regarding the respondents of pilot testing in respective circumstances like ‘How to conduct and whom to include in the sample?’ is one of the most frequently asked questions in survey research. The prime aim of this study is to provide clear guidelines for future researchers to increase their research reliability. In the first phase we have reviewed and discussed different pilot studies. Secondly, we reviewed the suggested and adopted rules related to pilot testing. In the last, we present the findings/guidelines based on analysis of the different studies. This step to by step guidelines does not provide only researchers the basic understanding of how to conduct pilot testing but also enhances their understanding regarding the importance of the validity and reliability of their studies.